La0.6Sr0.4Fe0.8Co0.2O3-δ electrophoretic coating for oxygen transport membranes. (February 2019) - Guironnet, L.; Geffroy, P.-M.; Jouay, F.; Pagnoux, C.; Richet, N.; Chartier, T.
Highlights: Electrophoretic deposition method of mixed conductor on the dense perovskite membrane. High electrochemical chemical performances of membranes with electrophoretic coating. The electrochemical chemical performances of membranes increase with the thickness of electrophoretic coating (up to 100 µm). Abstract: This work describes the development of electrophoretic deposition method for the elaboration of a porous coating on a dense membrane in order to improve its oxygen permeation performance. The dense membrane material produced from La0.5 Sr0.5 Fe0.7 Ga0.3 O3-δ perovskite is coated with La0.6 Sr0.4 Fe0.8 Co0.2 O3-δ perovskite layer by electrophoretic deposition method in order to improve the kinetics of oxygen surface exchanges. Then, the oxygen flux through the La0.5 Sr0.5 Fe0.7 Ga0.3 O3-δ dense membrane is largely impacted by La0.6 Sr0.4 Fe0.8 Co0.2 O3-δ electrophoretic coating, from 0.5 to 2.6 10 −3  mol⋅m −2 ⋅s −1 without and with La0.6 Sr0.4 Fe0.8 Co0.2 O3-δ coating after heating at 900 °C, respectively. Besides, a large impact of the thickness of the electrophoretic coating on the oxygen flux through the membranes is observed. The electrophoretic deposition has shown to be a powerful elaboration method of membrane to produce gaseous oxygen with high purity.